2008
DOI: 10.1016/j.jss.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Induces Notch1 Signaling in Small Cell Lung Cancer Cells

Abstract: Background-Small cell lung cancer (SCLC) is an aggressive malignancy. Current treatments yield dismal survival rates. We have previously demonstrated that histone deacetylase (HDAC) inhibitors can inhibit neuroendocrine tumor growth. Activation of the Notch1 signaling pathway also impairs SCLC cell viability. In this study, we investigated the ability of the HDAC inhibitor valproic acid (VPA) to activate Notch1 signaling and inhibit proliferation in SCLC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
5
46
0
1
Order By: Relevance
“…Th e cells formed of treated with NaVP cells formed smaller tumors as well. Previous studies have shown in vitro eff ect of NaVP on the other SCLC cell line DMS53, when treatment with NaVP concentrations as low as 1 mM signifi cantly impaired the cell mitochondrial activity, while higher concentrations (6 mM -10 mM) of NaVP resulted in the absence of tumor markers [15]. Similar results have been shown testing valproic acid on diff erent tumor cell lines other than SCLC.…”
Section: Discussionsupporting
confidence: 73%
“…Th e cells formed of treated with NaVP cells formed smaller tumors as well. Previous studies have shown in vitro eff ect of NaVP on the other SCLC cell line DMS53, when treatment with NaVP concentrations as low as 1 mM signifi cantly impaired the cell mitochondrial activity, while higher concentrations (6 mM -10 mM) of NaVP resulted in the absence of tumor markers [15]. Similar results have been shown testing valproic acid on diff erent tumor cell lines other than SCLC.…”
Section: Discussionsupporting
confidence: 73%
“…The NOTCH1 signaling pathway is silenced in many neuroendocrine malignancies, including SCLC (40). Activation of NOTCH1 signaling inhibited the growth of SCLC cells (25), and Genomic profiling of SCLC is still in its infancy, delaying the development of molecularly targeted therapies. Our approach to use combination therapy with CBL0137 and cisplatin is an important means to circumvent the development of resistance to standard therapy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of NOTCH has been identified in many cancers, including NSCLC (22), T-ALL (23), and GBM (24). In contrast, NOTCH1 signaling is suppressed in neuroendocrine tumor cells, including SCLC (25,26), indicating that inducing its expression is an attractive strategy for treating these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches revealed up-regulation of Bak protein expression, degradation of cyclin D1 and an increase in cyclin-dependent kinases p21 and p27 after sodium valproate treatment. In addition, sodium valproate also increased the levels of full-length Notch-1 and active Notch-1 intracellular domain, which intern inhibit proliferation and induced apoptosis of neoplasm (Greenblatt et al, 2007;Fortunati et al, 2008;Platta et al, 2008). Sami et al in cervical cancer found that sodium valproate can increase the expression of histone H3 acetylation and up-regulate p21 expression (Sami et al, 2008).…”
Section: 6429 Effects Of Sodium Valproate On the Growth Of Human Ovamentioning
confidence: 97%